Cultural sensitivity in health promotion program: Islamic persuasive communication - Ahmad, Mohd Khairie (2008)
Although scenarios in global health are witnessing benefits from new medicines and technologies, nonetheless there are unprecedented reversals. As a result, the World Health Organization has encouraged more innovative approaches in promoting health risk reduction and the reconsideration of risky lifestyle behaviour.The concept of culture sensitivity has emerged as a key topic of interest to health communication. The growing awareness about culture argues both for a shift in the philosophical and theoretical approaches, and in methods underpinning health communication. On the other hand, a lack of understanding of Muslims and their cultural and religious tradition contributes to potential conflicts in health promotion.Thus, based on present study involves health promotion policy makers, implementers, and health practitioners, this paper suggests the use of Islamic values and elements in developing a strategy for communicating health promotion. In specific, this paper has three main objectives: (1) to briefly review the research on cultural sensitivity factor with focus on religious factors in health communication; (2) to discuss what are the values and characteristics that formulate Islamic persuasive communication in general and in health promotion specifically; and (3) to discuss the constrain and challenges of Islamic persuasion in promoting health. This insight may contribute to further development of health promotion strategy for Muslim in Islamic nations as well as Muslim communities in non-Islamic nations through interculturalisation process.